PEMBELAJARAN IPS BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Muchtar, Fitri Yanty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to examine the concept of local wisdom-based social studies learning in elementary schools as an effort to strengthen students’ contextual understanding, social literacy, cultural awareness, and character development. Social studies in elementary schools has a strategic role in introducing learners to social life, cultural diversity, community values, and responsible citizenship. This article was written using a literature review method by analyzing relevant books, journal articles, and conceptual studies related to elementary social studies, local wisdom, contextual learning, and character education. The study shows that integrating local wisdom into social studies learning can make learning more meaningful, contextual, and reflective. Local traditions, cultural values, community practices, folklore, local economic activities, historical sites, and social institutions can be used as learning resources to help students understand social concepts from their immediate environment. Local wisdom-based social studies learning can also encourage students to appreciate cultural diversity, develop social concern, preserve local culture, and build responsible attitudes as members of society. Keywords: social studies learning, elementary school, local wisdom